Problematika Hukum Eksekusi Aset Kripto dalam Proses Kepailitan di Indonesia - Christopher Alexius Alfa Mulya (INDO PUBLISHING, 2026)
The advancement of digital financial technology has introduced crypto assets as an increasingly popular investment instrument, yet simultaneously generates novel legal issues when their owners are declared bankrupt. This study aims to analyze the legal standing of crypto assets as part of the bankruptcy estate (boedel pailit) and the problems surrounding their execution under Indonesian bankruptcy law. A normative juridical method is employed, utilizing statutory and comparative law approaches. The findings reveal that crypto assets qualify as part of the bankruptcy estate pursuant to Article 21 of Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations in conjunction with Articles 499 and 1131 of the Civil Code, as well as OJK Regulation Number 27 of 2024. Nevertheless, the execution of crypto assets faces three principal challenges: identification and seizure difficulties arising from the decentralized nature of crypto, the absence of a standardized valuation method for highly volatile assets, and the inadequacy of conventional auction mechanisms. Solutions are proposed in layers, through optimizing existing legal norms and reforming the Bankruptcy Law by adapting the framework of the European Union's Markets in Crypto-Assets Regulation.